TATAKELOLA WILAYAH SUMBER MATA AIR TIRTO ARUM, DESA SRIMULYO, KECAMATAN DAMPIT KABUPATEN MALANG - Sinollah Sinollah (UNUSA Press, 2019)
Tirto Arum water source is the only source of water that continues to flow despite dry season, especially in the Krajan Hamlet, Srimulyo Village, Dampit District, Malang Regency. This water source has been managed and has been distributed to 196 households. On February 20, 2019 the water pump was damaged due to a landslide. In addition, a 7.5 PK water pump engine with a capacity of 80 meters is used to flow water with a capacity of 100 meters, beyond the engine's working capacity, so that the connecting of connector between dynamo and fan inside the engine is released. By ownership, water sources and reservoirs are still private property. The purpose of this activity is providing assistance in managing Tirto Arum water source by involving the management, BPD and community in the Srimulyo Village. The approach used cross-program collaboration with managers, cross-sector collaboration with village officials and Participatory Rural Appraisal (PRA) communities’ approach. The results of this activity are: 1). The re-functioning of water pump machine to drain water from Tirto Arum water source to the reservoir which is then distributed to residents; 2). the arrangement of Tirto Arum water source environment by cleaning landslides and making the retaining wall landslide using sacks filled with soil and sand; 3). The Tirto Arum water source officially belongs to Srimulyo Village, as well as the land occupied by water reservoir with the signing of a grant agreement in writing on the stamp between the owner of water source (Mr. Wagiman) and Tandon land owner (Bapak Mul) with Srimulyo Village (represented by the Head of Village); 4). The signing of MoU between Unira Malang (represented by the Chairperson of LPPM) and Srimulyo Village Government (represented by the Head of Village) as the initial step for implementation of the Higher Education Tridharma in Srimulyo Village. Keywords: Governance, Tirto Arum water source